Phenolic Compounds and Pharmacological Potential of Lavandula angustifolia Extracts for the Treatment of Neurodegenerative Diseases - Olha Mykhailenko; Viktoriia Hurina; Nataliia Herbina; Yuliia Maslii; Liudas Ivanauskas; Inna Vladymyrova; Dmytro Lytkin; Zigmantas Gudžinskas; Hanna Severina; Olena Ruban; Victoriya Georgiyants (Plants)
The search for neuroprotective compounds in lavender is driven by its traditional use for brain health, with antioxidant activity serving as a key mechanism in reducing oxidative stress and supporting cognitive function. Lavender’s potential to protect neurons is based on its calming, anti-stress properties, which increase the brain’s resistance to neurodegeneration. Although lavender is not a traditional medicinal plant in Ukraine, it is increasingly recognised for its medicinal properties and is widely cultivated in the country. Lavender use in Ukraine is influenced by both global herbal practices and local medical traditions. The aim of this study was to optimise the preparation of lavender herb extracts, perform chemical profiling and evaluate their antioxidant and neuroprotective activities. The study focused on Lavandula angustifolia cultivated in Lviv, Ukraine. Modern analytical methods were used, including HPLC, spectrophotometry, molecular docking, lyophilisation and pharmacological testing. The selection of the optimal conditions for obtaining lavender herb extracts was determined on the basis of the results of the total yield of phenolic compounds in each extract, where it was found that the raw material–solvent ratio (1:10) in water and 50% ethanol gave the highest yield of substances; the preferred extraction time was 20 min, and the temperature was 60–70 °C, especially for water extraction. Further HPLC analysis identified marker compounds including rosmarinic acid (28.31 mg/g), chlorogenic acid (1.64 mg/g) and luteolin (0.23 mg/g) in the lyophilised ethanol extract, which were previously recognised as neuroprotective markers by molecular docking. The water extract showed higher antioxidant (total 50.85 mg/g) and neuroprotective activity, probably due to synergistic interactions among the components. Behavioural tests further demonstrated the neuroprotective potential of lavender herb. These results demonstrate the potential neuroprotective activity of lavender herb and open new possibilities for its use in the treatment of various neurodegenerative diseases.